Mobile Messaging Apps and Boundary Management Among Asian Hospitality Workers in New Zealand - Chueawatthanakun, Weeranart (Auckland University of Technology, 2026)
Mobile instant messaging (MIM) applications such as WhatsApp, LINE, and Microsoft Teams are now widely used in hospitality workplaces to support daily communication and coordination. While these platforms can improve efficiency, they can also extend work-related contact into personal time and affect employees’ work–life boundaries and wellbeing. This study explores how Asian hospitality workers in New Zealand experience and uses MIM in their everyday work and after-hours, and how these practices are shaped by values, work ethics, and workplace expectations. This study adopted an interpretivist qualitative approach. Semi-structured interviews were conducted with 11 Asian hospitality workers employed in different roles and workplaces. The interview data were analysed using thematic analysis to identify patterns in participants’ experiences, meaning, and responses to workplace messaging. The findings show that MIM has become embedded in daily hospitality operations and functions as an informal communication infrastructure. Participants used messaging to coordinate tasks, manage shifts, and resolve operational problems. However, they also experienced strong expectations of responsiveness including outside scheduled working hours. Responsiveness was shaped by cultural values, personal work ethics, and concerns about professional reputation, job security and relationships with managers and colleagues. Many participants relied on personal strategies to manage work-related communication, such as muting notifications, delaying replies, or separating work and personal platforms. These strategies were often developed in the absence of clear organisational guidance. Continuous connectivity was associated with emotional pressure, tiredness, guilt, and reduced opportunity for rest and recovery. Over time, this contributed to digital strain and weakened work-life boundaries. This study highlights how digital communication, cultural values, and organisational practices interact to shape Asian hospitality workers’ everyday experiences. The findings emphasise the need for clearer communication guidelines, greater managerial awareness, and more supportive workplace practices to protect employee wellbeing in digitally connected hospitality environments.